Lixiviats Issus De La Décharge Publique De La Ville De Meknès: Calcul Et Résultat Du Bilan Hydrique - Hicham, Lekehal; Aziz, Bouchelta; Brahim, Benzougagh; Khalid, Mimich (European Scientific Journal, ESJ, 2016)
The leachate issued from the garbage dumps of the city of Meknes represents a great environmental threat as they are neither recovered nor treated before their discharge into the natural environment, thus constituting an important source of pollution to the water of the Boufekrane’s river and neighboring agricultural land to the dump. Thus is the need to quantify the rate of this type of effluent: in order to offer technical and economic solutions to its treatment or disposal. The amount of waste arriving at the dump is estimated to 554 tons per day in 2015 with 40% average moisture content and a loss of water in the percolate from 5 to 10%, thus the amount of water supplied by the waste is estimated at 88.8 m3 per day. The volume of runoff water from the inside of the dump to the outside is estimated to be 38 m3 per day while the volume from outside to inside is null or negligible given the topography. The infiltration in soil is negligible because the floor of the dump consists of lithological marl Miocene formations, rendering the dump waterproof. The area, consisting of 17 hectares, receives an effective average rainfall of 475 mm / year, producing a volume of 80750 m3 / year, equivalent to 221 m3 / day. The total volume of leachate is about 271 m3 per day.